BTB protein MdBT2 inhibits anthocyanin and proanthocyanidin biosynthesis by triggering MdMYB9 degradation in apple. (12th June 2018) - An, Jian-Ping; An, Xiu-Hong; Yao, Ji-Fang; Wang, Xiao-Na; You, Chun-Xiang; Wang, Xiao-Fei; Hao, Yu-Jin
Abstract: MdMYB9 is a positive regulator in the biosynthesis of anthocyanin and proanthocyanidin in apple. However, its posttranslational regulation is unclear. Here, we demonstrated that the BTB protein MdBT2 had a negative role in the biosynthesis of anthocyanin and proanthocyanidin. MdBT2 interacted with MdMYB9 and negatively regulated the abundance of MdMYB9 protein through the 26S proteasome system. The degradation of MdMYB9 by MdBT2 reduced the expression of MdMYB9 -mediated anthocyanin and proanthocyanidin-related genes and reduced the accumulation of anthocyanin and proanthocyanidin, which functioned in an MdCUL3 -independent pathway. Our results indicated that MdBT2 negatively regulated the stability of MdMYB9, which provides new insight into the homeostasis of anthocyanin and proanthocyanidin in apple.